2010
DOI: 10.1097/qad.0b013e3283377a1e
|View full text |Cite
|
Sign up to set email alerts
|

HIV+ elite controllers have low HIV-specific T-cell activation yet maintain strong, polyfunctional T-cell responses

Abstract: Objective HIV+ elite controllers are a unique group of rare individuals who maintain undetectable viral loads in the absence of antiretroviral therapy. We studied immune responses in these subjects to inform vaccine development, with the goal of identifying the immune correlates of protection from HIV. Methods We compared markers of cellular activation, HIV-specific immune responses, and regulatory T (Treg) cell frequencies in 4 groups of subjects: HIV-negative healthy controls, elite controllers (HIV RNA le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 55 publications
6
112
2
2
Order By: Relevance
“…However, the circulating frequency of CD4 + Treg cells has not been found to show any correlation with the magnitude of HIV‐specific T‐cell responses,276, 277, 278 leaving the contribution of CD4 + Treg cells to regulation of virus‐specific T‐cell responses in HIV‐infected individuals unclear. Their role in suppressing immune activation is also uncertain.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…However, the circulating frequency of CD4 + Treg cells has not been found to show any correlation with the magnitude of HIV‐specific T‐cell responses,276, 277, 278 leaving the contribution of CD4 + Treg cells to regulation of virus‐specific T‐cell responses in HIV‐infected individuals unclear. Their role in suppressing immune activation is also uncertain.…”
Section: Regulatory Cell Populations and Their Relationship To Bnab Imentioning
confidence: 99%
“…Interestingly, elite controllers, a rare population of individuals that can maintain undetectable HIV viral loads in the absence of HAART, demonstrated higher frequencies of Treg cells compared to individuals on HAART (Chase, Yang et al, 2008). On the other hand, Owen et al, showed that individuals on HAART had higher frequencies of Tregs compared to elite controllers (Owen, Heitman et al, 2010). In contrast yet again, more recent studies have demonstrated that elite controllers have a lower level of Treg cells compared to viremic individuals, but that this "low" level of Tregs is similar to that observed in HIV positive individuals with viral load controlled by HAART (Brandt, Benfield et al, 2011).…”
Section: Treg In Hiv Infectionmentioning
confidence: 99%
“…Antiretroviral treatment (ART) during chronic HIV-1 infection results in a shift to a memory response composed of a polyfunctional phenotype that has also been observed in individuals who spontaneously control HIV-1 replication [8,9].…”
mentioning
confidence: 99%